Kandungan protein sel tunggal dalam kombinasi tape jerami dan limbah singkong menggunakan kapang Saccharomyces cerevisiae - Ramaiyulis; Suri Suciani; Novadhila Rahmi; Salvia Sani; Muthia Dewi (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Rice straw and cassava waste are abundant agricultural byproducts, but they have limitations in nutritional value, particularly low protein content. This study aims to evaluate the effect of a combination of straw and cassava substrates, as well as the addition of Saccharomyces cerevisiae mold, on increasing the content of single cell protein (SCP), crude protein, pure protein, microbial biomass, and pH stability during fermentation. The study was conducted experimentally with a 2×2 factorial completely randomized design (CRD) using four treatments: JKN (straw + cassava peel without yeast), JKR (straw + cassava peel + yeast), JSN (straw + cassava without yeast), and JSR (straw + cassava + yeast). Fermentation was carried out for 7 days under anaerobic conditions. The results showed that the JSR treatment produced the highest SCP (47.59 mg/mL) and the largest microbial biomass (4.37 mg/mL), while JSN produced the highest crude protein (13,40%) and pure protein (9,61%). The addition of yeast significantly increased PST and biomass, but in some treatments, it decreased the pure protein content. The combination of straw and cassava has been shown to increase the nutritional value of feed ingredients through the fermentation process, with effectiveness depending on the type of substrate and the presence of microbial inoculum.